Creep and damage investigation of advanced martensitic chromium steel weldments for high temperature applications in thermal power plants. (January 2015) - Schlacher, C.; Béal, C.; Sommitsch, C.; Mitsche, S.; Mayr, P.
<x content-type="archive" xml:space="preserve">Abstract</x> With the aim to increase base material creep strength and overcome the type IV cracking problem, a new design concept was developed. This so called martensitic boron–nitrogen strengthened steel (MARBN) combines boron strengthening through solid solution with precipitation strengthening by finely dispersed nitrides. In this work, uniaxial creep tests of the MARBN base material and welded joints have been carried out. The creep strength of the welded joints was analysed, and the evolution of creep damage was investigated. The creep tests of MARBN revealed increased strength of the base material of about +20% compared to the best commercially available 9Cr steel grade. At higher stress levels, the creep strength of crosswelds is between that of the MARBN base material and the conventional 9Cr base materials. Nevertheless, long term creep tests revealed a drop in creep strength of the MARBN welded joints. The underlying phenomena of crossweld creep behaviour are discussed in detail.